Implementation of Free Universal Health Coverage (UHC) by the Social Security Administering Body (BPJS) Reviewed From the Perspective of Health Law - Susi Sulastri; N. Ike Kusmiati (Dinasti Research, 2026)
This study examines the implementation of free health insurance under the Social Security Administering Body (BPJS) within the framework of Universal Health Coverage (UHC) in Indonesia from a health law perspective. The main objective is to analyze the extent to which legal regulations governing BPJS are effectively implemented and aligned with the principles of justice, legal certainty, and legal protection. This research employs a normative juridical design, utilizing statutory and conceptual approaches. The data sources consist of secondary data, including laws and regulations, academic literature, and relevant policy documents, which are analyzed using qualitative descriptive methods. The findings indicate that although the legal framework supporting BPJS and UHC is relatively comprehensive, its implementation faces several challenges. These include inaccuracies in beneficiary data targeting, disparities in healthcare service distribution, administrative inefficiencies, and limited legal protection for both patients and healthcare providers. Such issues demonstrate a gap between normative legal provisions and practical realities, thereby hindering the optimal realization of UHC objectives. The study concludes that while free BPJS has significantly expanded healthcare access and reduced financial barriers, its effectiveness depends on improvements in governance, legal enforcement, and institutional coordination. Strengthening regulatory consistency, enhancing data systems, and improving service delivery mechanisms are essential to achieving equitable and sustainable healthcare. This research contributes to the development of health law and policy by providing recommendations to optimize UHC implementation in Indonesia.